2005
DOI: 10.1091/mbc.e04-10-0939
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead-associated Domain Protein Cep170 Interacts with Polo-like Kinase 1 and Serves as a Marker for Mature Centrioles

Abstract: We report the characterization of Cep170, a forkhead-associated (FHA) domain protein of previously unknown function. Cep170 was identified in a yeast two-hybrid screen for interactors of Polo-like kinase 1 (Plk1). In human cells, Cep170 is constantly expressed throughout the cell cycle but phosphorylated during mitosis. It interacts with Plk1 in vivo and can be phosphorylated by Plk1 in vitro, suggesting that it is a physiological substrate of this kinase. Both overexpression and small interfering RNA (siRNA)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
260
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(274 citation statements)
references
References 50 publications
13
260
1
Order By: Relevance
“…Moreover, overexpression of AZI increases cell proliferation and promotes cell transformation (Keren-Paz et al, 2006;Kim et al, 2006) and high levels of AZI have been observed in gastric tumors (Jung et al, 2000). Our results show that overexpression of AZI induces aberrant synthesis of daughter centrioles as reported previously for the papillomavirus-16 E7 oncoprotein (Guarguaglini et al, 2005). We have now identified AZI overexpression as an alternative cause for daughter centriole overamplification again suggesting that the antizyme 1/AZI system regulates centriole synthesis.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, overexpression of AZI increases cell proliferation and promotes cell transformation (Keren-Paz et al, 2006;Kim et al, 2006) and high levels of AZI have been observed in gastric tumors (Jung et al, 2000). Our results show that overexpression of AZI induces aberrant synthesis of daughter centrioles as reported previously for the papillomavirus-16 E7 oncoprotein (Guarguaglini et al, 2005). We have now identified AZI overexpression as an alternative cause for daughter centriole overamplification again suggesting that the antizyme 1/AZI system regulates centriole synthesis.…”
Section: Discussionsupporting
confidence: 84%
“…These findings highlight that the HPV-16 E7-induced generation of immature daughter centrioles (Guarguaglini et al, 2005) is an active process with specific molecular requirements and not simply a consequence of cytokinesis defects, ploidy alterations or aberrant centriole splitting . It has been shown that other events leading to a deregulation of CDK2 activity such as loss of p16 INK4A can also stimulate abnormal centriole numbers following S phase arrest (McDermott et al, 2006).…”
Section: Rna Polymerase II Transcriptionmentioning
confidence: 76%
“…Lastly, depletion of cyclin A2 has been suggested to cause changes in ploidy (Mihaylov et al, 2002). However, there is no indication so far that cells with altered ploidy cannot undergo additional rounds of centriole duplication (Mantel et al, 1999;Guarguaglini et al, 2005). We therefore interpret the abrogation of HU-induced centriole overduplication in cyclin A2 siRNA-transfected cells (Figure 4d) as a result of a depletion of a critical factor for centriole overduplication under conditions of a prolonged S phase.…”
Section: A-amanitin Inhibits Hpv-16 E7-and Hu-induced Centriole Overdmentioning
confidence: 77%
See 2 more Smart Citations